2014
DOI: 10.1038/bmt.2014.216
|View full text |Cite
|
Sign up to set email alerts
|

Impact of rabbit ATG-containing myeloablative conditioning regimens on the outcome of patients undergoing unrelated single-unit cord blood transplantation for hematological malignancies

Abstract: This study aimed to assess the impact of antithymocyte globulin (ATG) on patient outcome in a retrospective series of 91 patients (median age: 12 years) who underwent unrelated single-unit cord blood transplantation (allo-CBT) following a myeloablative conditioning regimen. Cord blood units were HLA-matched (6/6, n = 18; 21%), one-Ag mismatched (n = 30, 35%) or two-Ag mismatched (n = 38; 44%). In this series, the OS, nonrelapse mortality (NRM) and cumulative incidence of relapse were 47 ± 6%, 23 ± 4% and 48 ± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 33 publications
8
27
0
Order By: Relevance
“…The current study also confirmed a detrimental impact of ATG on NRM as recently reported in a study including data from patents given UCB after MAC conditioning [25] or RIC in the double UCBT setting [26]. Further, despite ATG not only induces in vivo T-cell depletion of the graft but also promotes the generation of regulatory T cells [27, 28], ATG failed to prevent GVHD in the current study.…”
Section: Discussionsupporting
confidence: 89%
“…The current study also confirmed a detrimental impact of ATG on NRM as recently reported in a study including data from patents given UCB after MAC conditioning [25] or RIC in the double UCBT setting [26]. Further, despite ATG not only induces in vivo T-cell depletion of the graft but also promotes the generation of regulatory T cells [27, 28], ATG failed to prevent GVHD in the current study.…”
Section: Discussionsupporting
confidence: 89%
“…Another important difference is the use of ATG, mainly in patients undergoing SUCBT. Retrospective analyses have found ATG to be associated with worse outcomes after myeloablative and reduced intensity conditioning in the setting of UCBT [4244]; possibly due to a delayed immune recovery with ATG and increased incidence of post-transplantation lymphoproliferative disorder and infections [43, 4548]. …”
Section: Discussionmentioning
confidence: 99%
“…In the largest retrospective study, survival was lower with ATG (w10 mg/kg between day -5 and 0) than without ATG (61% versus 71%), however, this was not statistically significant [83]. In the second largest retrospective study, survival was significantly lower with ATG (median 5 mg/kg between approximately day -6 and -5) than without ATG (38% versus 57%; P ¼ .02) [86].…”
Section: Impact Of Atg In Conditioning On Gvhd Relapse Infections Amentioning
confidence: 94%